Analisis Peran Responsible Leadership dan Work-Life Balance Tim Pengajar terhadap Kepuasan Belajar Peserta Didik: Analysis of the Role of Responsible Leadership and Work-Life Balance of the Teaching Team on Student Learning Satisfaction - Tara, Rony Umbu Hina; Surbakti, Nadya Faresa; Simamora, Marlini Afrida Br; Skono, Paulina; Alung, Septiana; Djami, Avlin Anggelina Rosianti Frans (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2024)
Student learning satisfaction is a significant indicator of success in the educational process. As learning facilitators, educators play an essential role in fostering a conducive academic environment. This study examines the influence of responsible leadership and work-life balance among teaching staff in enhancing student learning satisfaction. Responsible leadership, which highlights the principles of social responsibility and ethics, significantly impacts the quality of teacher-student interactions. Work-life balance enables teachers to carry out their duties effectively without undue stress. This study used a quantitative approach through a survey of 200 students. This study's findings indicate a significant relationship between responsible leadership and student learning satisfaction. Teachers who apply responsible leadership principles, such as transparency, ethics, and concern for student welfare, can create better relationships with students. Responsible leadership facilitates more effective communication between teachers and students and creates a sense of security and emotional support, ultimately contributing to increased learning satisfaction. In addition, the study's results also revealed that work-life balance positively impacts the quality of students' learning experiences. Teachers who can balance their personal and professional lives tend to be more focused, less stressed, and more ready to give their full attention to students. This study shows that teachers who balance work and personal life have higher levels of job satisfaction, which is reflected in how they manage their classes and interactions with students. Teachers who are more satisfied with their work-life balance are able to create a more positive atmosphere, which can increase student learning satisfaction.